2010
DOI: 10.1001/archpediatrics.2009.268
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Plasma Glucose Levels Within the Normoglycemic Range in Childhood as a Predictor of Prediabetes and Type 2 Diabetes in Adulthood

Abstract: To determine whether childhood elevated fasting plasma glucose (FPG) levels within the normoglycemic range predict diabetes in adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
66
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 24 publications
15
66
3
Order By: Relevance
“…In response to a glucose challenge, the ACI strain shows only a slight increase in plasma insulin levels, with a very low IGI, indicating decreased beta cell function. In addition to being glucose intolerant, the ACI is the only strain to exhibit increased fasting glucose levels, a known predictor of T2D (51,52). In contrast to the ACI, the WKY strain shows elevated fasting insulin and an increased insulin response to a glucose challenge, as previously demonstrated (35,63).…”
Section: Discussionsupporting
confidence: 54%
“…In response to a glucose challenge, the ACI strain shows only a slight increase in plasma insulin levels, with a very low IGI, indicating decreased beta cell function. In addition to being glucose intolerant, the ACI is the only strain to exhibit increased fasting glucose levels, a known predictor of T2D (51,52). In contrast to the ACI, the WKY strain shows elevated fasting insulin and an increased insulin response to a glucose challenge, as previously demonstrated (35,63).…”
Section: Discussionsupporting
confidence: 54%
“…This is before other morbidities compound the diagnosis and may be due to attrition of beta cells occur over time [43]. It is of interest in these studies a fasting glucose value of 86 mg/dL was found as a cut-point of being potentially abnormal (Table 1) [44]. Obesity was the most consistent predictor of the MetS from adulthood, preceding the onset of high insulin levels [45].…”
Section: Predictors Of Prediabetes and Diabetesmentioning
confidence: 98%
“…Waist circumference ≥90th percentile and waist-to-hip ratio >0.5 are used as an index of central obesity for children between 10 and 16 ages. We recommend that fasting glucose ≥86 mg/dL [44], triglyceride ≥100 mg/dL, HDL-C < 45 mg/dL, and blood pressure ≥115 mmHg systolic or ≥75 mmHg diastolic can be considered as abnormal values for children (Table 1). Similarly, for adolescents over 16 years of age, criteria can be modified as FPG ≥ 100 mg/dL or known T2DM, triglyceride ≥100 mg/dL or specific treatment for high triglyceride, HDL-C < 45 mg/dL for males and <50 mg/ dL for females, or specific treatment for low HDL-C and systolic blood pressure ≥115 mmHg or diastolic blood pressure ≥75 mmHg or treatment of previously diagnosed hypertension.…”
Section: Existing Definitions For Metabolic Syndrome In Youthmentioning
confidence: 99%
“…The children with high fasting blood glucose have 49% lower glucose deposition index (504). More importantly, children with elevated fasting blood glucose were 3.4 and 2.1 times more likely to develop prediabetes and diabetes, respectively, as adults (378). …”
Section: Primary Prevention Of Physical Inactivity: Childhood Devmentioning
confidence: 99%